Dual career couples in R&D labs - Bradbury, Susan L.
Susan L. Bradbury reports on a study that shows it is beneficial for employers of professionals to locate in metropolitan areas.
Large urban areas offer advantages for recruiting and retaining the growing number of dual career couples, a study shows.
Location can affect a firm's ability to recruit and retain professional employees. Location also influences the characteristics of the local labor market from which the firm draws its employees. Location preferences differ among household groups, with dual career couples particularly constrained and attracted to large metropolitan centers. The findings of this study suggest that it is beneficial not only for employees but for employers of professionals to locate in metropolitan areas. Companies that fail to consider the dual career couple as a unique employee group may not recognize the counterproductive nature of their personnel policies and procedures and, as a result, may lose top professionals.